2010
DOI: 10.1007/s00276-010-0676-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic basis of ulnar index metacarpal reverse flow vascularized bone graft for index distal bone loss

Abstract: Well-known advantages of vascularized bone grafts led us to determine the anatomical basis of a metacarpal vascularized bone graft to find a solution for distal index bone loss. Seventeen adult human hands from fresh cadavers were dissected and analyzed. For each hand, we studied the second dorsal metacarpal artery, the ulnar dorsal proper digital artery of index, and the ulnar palmar proper digital artery of the index. Location, diameters, origins, and anastomoses were observed, and at the end, the vascularis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…The cutaneous vascular supply of the dorsum of the hand arises from perforators of the dorsal metacarpal arteries (DMCA), with the SDMA most commonly branching off the dorsal carpal arch, and less commonly from the radial artery or FDMA . The SDMA has two venae comitantes and runs along the suprafascial planes of dorsal interosseus muscle in the second webspace, adjacent to the second metacarpal on its ulnar border and beneath extensor indicis tendon. Anastomotic networks between the dorsal and palmar metacarpal artery systems are also well described, found in most abundance distal to the conjoint tendon in the intermetacarpal space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cutaneous vascular supply of the dorsum of the hand arises from perforators of the dorsal metacarpal arteries (DMCA), with the SDMA most commonly branching off the dorsal carpal arch, and less commonly from the radial artery or FDMA . The SDMA has two venae comitantes and runs along the suprafascial planes of dorsal interosseus muscle in the second webspace, adjacent to the second metacarpal on its ulnar border and beneath extensor indicis tendon. Anastomotic networks between the dorsal and palmar metacarpal artery systems are also well described, found in most abundance distal to the conjoint tendon in the intermetacarpal space.…”
Section: Discussionmentioning
confidence: 99%
“…While the anatomical basis for a reverse‐flow vascularized bone flap based on the SDMA for index distal phalanx reconstruction has been described, the current paper describes a clinical case of a reverse‐flow SDMA vascularized bone flap for index distal bony loss.…”
mentioning
confidence: 99%
“…However, the main focus was on the palmar side of the bone. 10,[33][34][35][36][37] Moreover, Earley 38 and Yousif et al 39 found in their cadaveric dissections that the second dorsal metacarpal artery is often larger than the first. 14 Uysal and colleagues 12 described in their detailed dissection study in 18 cadaveric hands that the dorsal metacarpal arteries arise from the dorsal carpal network and course along the metacarpal bones closer to the ulnar border supplying their periosteum through the muscular branches.…”
Section: Discussionmentioning
confidence: 99%
“…Leurs anastomoses avec le réseau dorsal des doigts permettent même leur utilisation avec un point de rotation distal [19].…”
Section: Les Artères Métacarpiennes Dorsalesunclassified
“…Parmi ces artères, toutes donneuses potentielles de greffon osseux, c'est la deuxième qui a été étudiée ; elle a un diamètre de 1 à 1,5 mm, chemine sur le deuxième interosseux dorsal, et s'anastomose avec le réseau palmaire par un rameau perforant ; elle permet de lever un fragment cortico-spongieux à partir du col du deuxième métacarpien avec un pédicule proximal long de 5 à 7 cm permettant d'atteindre le scaphoïde et les autres os du carpe [20], ou un pédicule distal permettant d'atteindre la phalange distale de l'index [19]. [21,22,23] L'ulna est vascularisée par : une artère nourricière, qui pénètre par la face antérieure au quart proximal [21], qui a un trajet ascendant, et se divise en une branche ascendante et une branche descendante ; pour Forriol Campos et al [24], le ou les foramen(s) nourricier(s) est(sont) situé(s) entre 25 et 50 % de la longueur totale de l'os ; pour Kizilkanat et al [25], ils sont situés entre 27 et 54 % de la longueur totale de l'ulna ; Longia et al [26] en ont observé jusque trois ou quatre par os ; des artères périostées, nombreuses au niveau du processus coronoïde et de l'olécrâne [21], semblant assurer la vascularisation du tiers distal de l'os, grâce à une disposition en anneau étagés, reliés entre elles par des anastomoses longitudinales [21] et aux rameaux de la branche descendante de l'artère nourricière, qui en naissent à intervalles réguliers [21].…”
Section: Les Artères Métacarpiennes Dorsalesunclassified